Functional dependence and type 2 diabetes mellitus in elderly subjects covered by Peruvian Social Security: analysis of ENSSA-2015 - Ramirez-Ramirez, Rofilia (2020)
Objective: to estimate the prevalence of functional dependence and to assess its association with type 2 diabetes mellitus (DM) in elderly subjects registered in Peruvian Social Security (EsSalud) in 2015. Materials and methods: this is a secondary analysis of the National Socioeconomic Healthcare Access Survey performed in EsSalud members in 2915 (ENSSA-2015), a survey performed in households using two-stage probabilistic sampling that was representative at a national level of population registered in EsSalud. Functional dependence was assessed using the Katz index (≥ 1 point). DM was determined by participants’ self- report. Adjusted prevalence rates (aPR) were estimated according to potential confounding factors using multiple log-Poisson regression alongside their 95% confidence intervals (CI) and p-values. All analyses took into account the complex sampling used in ENSSA-2015. Results: nearly eleven thousand participants (10,985) out of 12,805 eligible subjects were included in the analysis. Prevalence values for partial and severe functional dependence were 12.9% (95% CI: 11.9–13.8) and 6.0% (95% CI: 5.3–6.7), respectively. The prevalence of functional dependence (partial or severe) in diabetic subjects was 23% higher than that of non-diabetics, after controlling for potential confounding factors (aPR 1.23; 95% CI: 1.04–1.44; p= 0.013). Conclusions: nearly one of five elderly subjects registered in EsSalud had some degree of functional dependence (partial or severe). Also, DM was associated with a greater likelihood for having functional dependence in this population.